2022
DOI: 10.3390/molecules27030907
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments of Liquid Chromatography Stationary Phases for Compound Separation: From Proteins to Small Organic Compounds

Abstract: Compound separation plays a key role in producing and analyzing chemical compounds. Various methods are offered to obtain high-quality separation results. Liquid chromatography is one of the most common tools used in compound separation across length scales, from larger biomacromolecules to smaller organic compounds. Liquid chromatography also allows ease of modification, the ability to combine compatible mobile and stationary phases, the ability to conduct qualitative and quantitative analyses, and the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…Protein-selective binding can be used to capture the tagged protein via a specific interaction. 37 For example, a His-tagged protein possessed chelating ligands in amine groups of histidine. This system has been widely applied in protein purification by using affinity chromatography, where nickel(II) ions are adhered to the membrane’s surface.…”
Section: Fundamentals Of An Affinity Membranementioning
confidence: 99%
See 2 more Smart Citations
“…Protein-selective binding can be used to capture the tagged protein via a specific interaction. 37 For example, a His-tagged protein possessed chelating ligands in amine groups of histidine. This system has been widely applied in protein purification by using affinity chromatography, where nickel(II) ions are adhered to the membrane’s surface.…”
Section: Fundamentals Of An Affinity Membranementioning
confidence: 99%
“…Furthermore, recent years have witnessed various affinity membranes specifically developed to target a particular protein. Protein-selective binding can be used to capture the tagged protein via a specific interaction . For example, a His-tagged protein possessed chelating ligands in amine groups of histidine.…”
Section: Fundamentals Of An Affinity Membranementioning
confidence: 99%
See 1 more Smart Citation
“…Mixed‐mode stationary phases might have characteristics of high separation selectivity, high loading capacity, and high separation efficiency compared to conventional single‐mode stationary phases [5–7] . Studies on mixed chromatography in the last decade have shown that mixed‐mode chromatography is a versatile approach for the simultaneous separation of highly mixed classes of analytes including highly polar, moderately polar, and nonpolar compounds [8–11] …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Studies on mixed chromatography in the last decade have shown that mixed-mode chromatography is a versatile approach for the simultaneous separation of highly mixed classes of analytes including highly polar, moderately polar, and nonpolar compounds. [8][9][10][11] The mixed-mode separation mechanism is achieved by using at least two chromatography subtypes together. For example, hydrophobic and hydrophilic interactions are often combined in column chromatography.…”
Section: Introductionmentioning
confidence: 99%